Meningkatkan Kemampuan Pemahaman Konsep Matematis Siswa Melalui Pembelajaran Kalaboratif MURDER - Marniati Marniati; Tahir Tahir (Jurnal Karya Pendidikan Matematika, 2022)
This research aims to determine the improvement of students' conceptual understanding skills with MURDER collaborative learning and student responses to the application of MURDER collaborative learning. This research is a research experiment (quasi experimental design) with the design of non-equivalent control group design. The population is all students of grade VII SMP Negeri 1 Lalolae as much as 54 people. Sampling with a totally sampling technique obtained the VIIA class as the experimental class and the VIIB class as the control class. The hypothesis test indicates that at the level of the significance α = 0.05, the value of tcount = 3,863 > ttable = 2,022. That means that H0 rejected and H1 accepted. So it can be concluded that MURDER collaborative learning can improve students' understanding of mathematical concepts. based on the results of the student response questionnaire analysis, the percentage of the average score for student responses was 84.68% and was included in the very good category.